PARTISPASI MASYARAKAT DAN DAMPAK KEBIJAKAN PEMBANGUNAN DERMAGA LAUT USUKU DI KABUPATEN WAKATOBI - La Ode Muhammad Elwan (Universitas Halu Oleo, 2018)
The objectives to be achieved in this study are: (1) Assessing the form of community participation in building the Usuku Jetty in Wakatobi Regency, and (2) Analyzing the impact of the construction of the Usuku dock in development (social, economic and environmental) in Wakatobi Regency. The method of this research is qualitative research using a descriptive approach. The results showed that: (1) The form of community participation in supporting the construction of the Usuku Jetty in Wakatobi Regency included: (a) idea/thought participation, b) goods participation, and (c) labour participation. The level of community participation in the construction of the Usuku jetty in Wakatobi Regency which reached the highest position was the participation of ideas and thoughts, then participation in material (goods), and the lowest was community participation in the form of energy, and (2) The impact of the construction of the Usuku Jetty in the development in Wakatobi Regency are as follows: (a) Economic aspects, the impact of the construction of Usuku jetty on economic aspects is seen from the emergence of new business units, the opening of employment, the increasing number of vessels berthed, and increased loading and unloading activities (b) Aspects socially, the impact of the construction of the dock on social aspects was seen as increasing crime around the Usuku jetty area, and increasing interaction among workers and (c) Environmental aspects, the impact of the construction of the Usuku Jetty on the environmental aspect, can be seen from seawater pollution and the amount of garbage that accumulates. Keywords: Community Participation, Impact of Policy, Development of Jetty.